Association of Carboxyhemoglobin Levels with Yogic Breathing in Medical Undergraduate Students- An Observational Cross-sectional Study - Choudhary, R; Yadav , PK (Journal of Indian Academy of Forensic Medicine, 2024)
Carbon monoxide is produced from incomplete combustion of fuels like charcoal, briquette, fuel gas, petroleum, using a burner, heater or cooking equipment with inadequate ventilation, faulty water heaters, exhaust fumes from vehicles, industries and cigarette smoking leading to high Carboxyhemoglobin levels. The effect of low-level exposure to carbon monoxide on the cognitive functions of an individual is not very well documented as the clinical syndrome in occult cases have a very obscure clinical presentation with little awareness and knowledge in this particular domain. The various neurological manifestations resulting from carbon monoxide exposure could range from headache, fatigue, dizziness, syncope, lethargy, coma, seizures and death at high levels. It has been observed that deep breathing exercises help in reducing the carboxyhemoglobin levels in smokers. Pranayama or yogic method of breath regulation is an important component of Yoga. We had conducted this study with the objective of analysing the association of Carboxyhemoglobin and Methhemoglobin levels with Yogic Breathing in healthy undergraduate medical students. Design- Analytical observational cross sectional study. Setting- Tertiary Medical teaching Institute. Participants- Healthy undergraduate medical students. Study Period- September 2023. Our study was carried out on a total of 42 undergraduate medical students. The oxygen saturation pattern in both the groups came out to be normal (>98%). We found a significant difference between the Pulse rate (p<0.05) and carboxyhemoglobin (p<0.02) in both groups. Yogic breathing is definitely a healthier way of breathing; hence adoption of such healthy practices should be encouraged worldwide.